2010
DOI: 10.1007/s12020-009-9301-0
|View full text |Cite
|
Sign up to set email alerts
|

Japanese cases of acute onset diabetic ketosis without acidosis in the absence of glutamic acid decarboxylase autoantibody

Abstract: We report consecutive Japanese patients presented with acute onset diabetic ketosis who had negative glutamic acid decarboxylase autoantibody (GADAb) to clarify the clinical characteristics of them. A total of consecutive 1,296 in-patients with newly diagnosed diabetes mellitus, who were admitted to our center from April 2003 to October 2008, were analyzed. Among them, 17 patients who presented with acute onset diabetic ketosis without acidosis, and found to be negative for GADAb, were included. They showed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Diabetic ketonuria is common among newly diagnosed or untreated patients with T2D and has been used to predict pathologic features or metabolic acidosis 14. Among Japanese patients with acute onset diabetic ketosis, there was a preponderance of males 24. The present study obtained similar results: T2DK was poorly controlled and male in the majority.…”
Section: Discussionsupporting
confidence: 77%
“…Diabetic ketonuria is common among newly diagnosed or untreated patients with T2D and has been used to predict pathologic features or metabolic acidosis 14. Among Japanese patients with acute onset diabetic ketosis, there was a preponderance of males 24. The present study obtained similar results: T2DK was poorly controlled and male in the majority.…”
Section: Discussionsupporting
confidence: 77%
“…He had consumed 1-3 liters of sweet beverages daily until admission, in an effort to quench his thirst. The observations made in this case, taken together, indicated that he was suffering from "soft-drink diabetic ketosis" [5]. The blood triglyceride and total cholesterol levels were extremely elevated, having reached 5,449 mg/dL and 718 mg/dL, respectively ( Table 2).…”
Section: Case Presentationmentioning
confidence: 75%
“…Soft-drink diabetic ketosis has an acute onset and is induced by excessive ingestion of sugar-containing soft drinks in obese type 2 diabetic patients, and has most commonly been reported in Japanese subjects [5][6][7]. Soft-drink diabetic ketosis shows a male predominance, a tendency for obesity, family history of type 2 diabetes mellitus, and patients are generally negative for antiglutamic acid decarboxylase (GAD) antibody.…”
mentioning
confidence: 99%
“…The present patient did not have such an event. In a report, however, about half of type 2 diabetes patients who developed DKA had no identifiable antecedent or concurrent stressful condition (8).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we diagnosed that her diabetes was type 2. Al- though DKA typically occurs in type 1 diabetes, it is also known to be occur in type 2 diabetes (7,8), under conditions such as serious infection, trauma, cardiovascular emergency, and omission of treatment (1). The present patient did not have such an event.…”
Section: Discussionmentioning
confidence: 99%